Super-resolution imaging of platelet-activation process and its quantitative analysis - Jinkyoung Chung (Nature Portfolio, 2021)
Abstract Understanding the platelet activation molecular pathways by characterizing specific protein clusters within platelets is essential to identify the platelet activation state and improve the existing therapies for hemostatic disorders. Here, we employed various state-of-the-art super-resolution imaging and quantification methods to characterize the platelet spatiotemporal ultrastructural change during the activation process due to phorbol 12-myristate 13-acetate (PMA) stimuli by observing the cytoskeletal elements and various organelles at nanoscale, which cannot be done using conventional microscopy. Platelets could be spread out with the guidance of actin and microtubules, and most organelles were centralized probably due to the limited space of the peripheral thin regions or the close association with the open canalicular system (OCS). Among the centralized organelles, we provided evidence that granules are fused with the OCS to release their cargo through enlarged OCS. These findings highlight the concerted ultrastructural reorganization and relative arrangements of various organelles upon activation and call for a reassessment of previously unresolved complex and multi-factorial activation processes.